Female Participation in Higher Education in the Context of Nepalese Society (Bhartiya Knowledge Systems, 2024)
Female participation in higher education in the context of Nepali society is research with aim to identify women's status to their Higher Education status in Lalitpur district and how the socio-economic and cultural status of women influences their educational attainment. This is quantitative research accomplished in survey design. The study tools used in this research were twenty-one closed-ended questionnaires. The questions were of the objective answer type and multiple-choice items. The population of this study was the people living in one Rural Municipality, one Municipality, and one Sub-Metropolitan City. The numbers of research participants were 379 female families’ heads of the three local level government of Lalitpur district. This research shows the significant relationship between qualification and different factors of female heads such as residence, caste, marital status, knowledge of ICT, and the knowledge of legal provision to their education and there are statistical differences between income and female engagement in higher education.